2021
DOI: 10.3892/ijmm.2021.5004
|View full text |Cite
|
Sign up to set email alerts
|

miR‑29a‑3p regulates the epithelial‑mesenchymal transition via the SPARC/ERK signaling pathway in human bronchial epithelial cells

Abstract: Neutrophilic asthma (NA) is a subtype of asthma that responds poorly to corticosteroid treatment. In certain diseases, microRNA (miR)-29a-3p is considered to be a key regulatory molecule for remodeling of the extracellular matrix. However, the effect of miR-29a-3p on airway remodeling is unknown. The present study aimed to investigate the role of miR-29a-3p in NA. A mouse model of NA was established and these animals were compared to normal controls. Both groups of mice were subjected to lung function tests an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…SPARC expression was increased in mouse models with an epithelial-mesenchymal transition phenotype and SPARC expression had an effect on lung function in both human bronchial epithelial cells and mouse models (53,54). The SPARC fragment binding with the present ligand protein inhibited tumor cell adhesion, while promoting spreading and stimulating tumor cell migration and invasion, suggesting an important effect of SPARC expression on lung cancer development and progression (55)(56)(57). Univariate analysis suggested that TNM stage, lymph node metastasis, distant metastasis and smoking history were associated with poor prognosis in patients with NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…SPARC expression was increased in mouse models with an epithelial-mesenchymal transition phenotype and SPARC expression had an effect on lung function in both human bronchial epithelial cells and mouse models (53,54). The SPARC fragment binding with the present ligand protein inhibited tumor cell adhesion, while promoting spreading and stimulating tumor cell migration and invasion, suggesting an important effect of SPARC expression on lung cancer development and progression (55)(56)(57). Univariate analysis suggested that TNM stage, lymph node metastasis, distant metastasis and smoking history were associated with poor prognosis in patients with NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Epithelium damage and deficiency have been reported to result in EMT, which is considered to be intricately involved in AR and is the main cause of fixed airflow limitations that occur during asthma attacks (26,71). In contrast, inhibition of the EMT process can alleviate AR in asthma.…”
Section: Discussionmentioning
confidence: 99%
“…As a member of the MAPK family, ERK1/2 transduces extracellular signals to intracellular signaling cascades, thereby regulating cell behaviors, including cell proliferation and differentiation [ 48 ]. Numerous studies have shown that the ERK/MAPK signaling pathway has crucial roles in tumorigenesis and metastasis [ 49 , 50 ]. HOXC6 has been shown to facilitate the proliferation and migration of glioblastoma cells by activating the ERK/MAPK signaling pathway [ 51 ].…”
Section: Discussionmentioning
confidence: 99%